PENGARUH KOMUNIKASI DAN INSENTIF TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING KOKARSI PT.SANKYU INDONESIA CILEGON - Deccasari, Dwi Danesty; Maulina; Marli (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2024)
This study aims to determine the Effect of Communication and Incentives on Employee Performance with Job Satisfaction as an Intervening Variable in PT. Sankyu Indonesia Cilegon's Kokarsi and to find out whether job satisfaction acts as an intervening variable. The research method uses quantitative causality methods with SPSS version 25 data processing. The sampling technique uses Simple Random Sampling with a sample of 40 employees using the slovin formula. Data analysis techniques used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis and path analysis. By using SPSS. The results of the job satisfaction variable (Z) as an intervening variable have a significant effect on employee performance (Y) with a regression coefficient value of 0.612 and a significance level of 0.000. The results of the T-test study show that the Communication Variable has a significant effect on Employee Performance. Incentive Variable has no significant and negative effect on Employee Performance. Job Satisfaction Variable has significant effect on Employee Performance. Communication Variable has no significant effect on Job Satisfaction. Incentive variable has significant effect on Job Satisfaction. Communication and Incentives on Employee Performance through Job Satisfaction as Intervening Variables have a significant effect on the simultaneous F test. This means that it can be interpreted that the variable job satisfaction (Z) partially mediates the relationship between the communication and incentive variables (X) on employee performance (Y).